Marasmius odoratus—a new jasmine-scented species of Marasmius section Globulares from India - Farook, V. Adnaan; Manimohan, Patinjareveettil (Phytotaxa, 2015)
Marasmius odoratus sp. nov. is described from Kerala State, India, based on morphological and molecular (ITS) phylogenetic data and is assigned to the section Globulares. Comprehensive description, photographs, and comparison with allied species are provided. It is characterized by a deeply sulcate pileus with grayish red grooves on a pale cream background, a long, pale cream to pale orange stipe, narrowly clavate basidiospores [17–23(–25) × 4–5 μm], a fragrant odor recalling jasmine flower, and a distinctive ITS sequence.